Feasibility of Vertical Rainwater Harvesting via In-situ Measurement of Wind-driven Rain Loads on Building Facades in a Tropical Climate (International Journal of Built Environment and Sustainability, 2021)
Rainwater is an alternative water resource to fulfill sustainable management of freshwater particularly in the regions receive abundant annual amounts of precipitation such as tropical Malaysia. To collect and store rainwater, rainwater harvesting system has been practiced since ancient from horizontal surfaces mostly rooftop of buildings in urban areas. Nowadays, this method in modern urban areas with tall buildings is considered inadequate and uneconomical because the ratio of facade surface areas is much higher than the ratio of roof surface areas. On the other hand, all rain has a horizontal velocity due to wind acting upon rain droplets which is called wind-driven rain (WDR). Growing tall buildings and the presence of WDR phenomenon make building façade surfaces the available promising surfaces to harvest substantial rainwater vertically and more efficiently. This article presents a one-year field measurement results that aims at quantifying the WDR loads impinged on the vertical facade areas of a pilot building located at the main campus of the University Malaya in Kuala Lumpur, Malaysia. Detailed descriptions of the gauge design, building, the measurements of on-site WDR, rainfall duration time, and weather data are presented. Records show that monsoon winds characteristics have significant influence on the WDR loads on the building facades compare to horizontal rainfall intensity. Finally, the collected in-situ data are exploited to validate data and determine WDR coefficient (γ) to estimate the amount of WDR on a building façade via an empirical WDR relationship. Results show the feasibility of each square meter of vertical façade area to supply 12% of non-potable or 4.9% of potable water-usage per capita per day.
Keywords: Wind-driven rain; Vertical Rainwater harvesting; Building façade; Measurement data; Monsoon wind